Video games and dystopia: Total cities, post-cities and the political unconscious. Issue 3 (1st September 2017) - Johnson, Craig; Tulloch, Rowan
Dystopian settings dominate the video game landscape. Social collapse and totalitarian repression are amongst the favourite scenarios depicted in this medium. In this article, we offer a reading of these dystopian visions, not just as an aesthetic choice or gameplay trend, but as reflective of a 'political unconscious' latent in these games. These games are products of a very particular set of political, cultural and historic contexts, and embody key contemporary fears and apprehensions. To trace this we focus on how the space of the city has come to be a key signifier and site of dystopian anxiety in these games. Specifically, we look at how the city functions in two video games, Fallout 3 and Mirror's Edge, to analyse the means and mechanisms through which game spaces manifest political logics. In doing so we ultimately seek to show how video games offer us insight into contemporary political change and order.